In Situ Creep Model Testing for the Tunnel Anchor Foundation of Xingkang Suspension Bridge in Luding of China - Lina Wen; Qiangong Cheng; Qiang Cheng; Xifeng Guo; Bin Zhang (Advances in Civil Engineering)
Due to the limitations of geography and geology, cast concrete tunnel anchors were used to provide counterforces for Xingkang Suspension Bridge foundation at the left bank of Daduhe River. In this study, the in situ creep tests were conducted on two model tunnel anchors at a scale of 1:10 near the real working anchor site. Thus, the long-term deformation of the real working tunnel anchors installed at the bridge foundation could be determined from the creep test of model tunnel anchors. The creep tests were conducted under three different loads and lasted for 102.2 h, 167.5 h, and 189.4 h, respectively. The model anchor, the surrounding rock, and their interface were all monitored and measured during the creep testing. In addition, the numerical calculation, in which the Burger creep constitution was used for describing the surrounding rock and the Mohr–Coulomb criterion for describing the concrete anchor, was performed to further evaluate the long-term stability of the real working tunnel anchors. The numerical calculations are in good agreement with the laboratory testing results, and the creep deformations of the anchor and the surrounding rock have the same order of magnitude. The results show that the tunnel anchor and surrounding rock of Xingkang Bridge are in a stable creep state under the three different loads.